Effect of an integrated active-lessons programme on vocabulary and narrative comprehension in pre-school children - Alba Cámara-Martínez; Sara Suárez-Manzano; Emilio J. Martínez-López; Alberto Ruiz-Ariza (South African Journal of Education, 2022)
The acquisition of vocabulary and narrative comprehension are key abilities for children’s literacy development and to potentiate cognitive and academic skills from early ages. The aim with this study was to analyse the effects of a 6-week integrated active-lessons programme based on playful games, vocabulary, and narrative comprehension. Ninety-two pre-school children (45.7% girls) aged 35.83 ± 2.57 months were split into experimental and control groups. Results from the pre- and post-intervention assessments show improvements of 56.1% in vocabulary (p < 0.001, Cohen’s d = 0.759) and 24.7% in narrative comprehension (p < 0.001, Cohen’s d = 0.710) in the treatment group. The results do not vary based on gender or age (31−36 and 37−42 months). Active lessons based on playful games within the classroom are suggested as support for the acquisition of vocabulary and narrative comprehension in childhood education.